Optimization of Centrifugal Pump Properties to Improve the Accuracy of Water Discharge and Pump Head Measurements - Azzizzah, Frida Amriyati; Soolany, Christian; Aji, Dhimas Oki Permata; Akil, Hilmi Maulana (Journal of Development Research, 2024)
Centrifugal pumps are extensively used in industries and water management systems, where accurate measurements of water flow rate and pump head are essential for evaluating performance. However, inaccuracies arising from suboptimal designs of training kits present challenges in educational environments. This study aimed to optimize a centrifugal pump training kit to enhance measurement accuracy and reliability. The research was conducted over four months, involving modifications to the impeller, casing, and pressure measurement systems, along with rigorous calibration to minimize errors. Measurements of suction pressure, discharge pressure, water flow rate, and pump head were repeated under standardized conditions to ensure data consistency. The results demonstrated significant improvements, with consistent measurements of suction pressure (21 inHg), discharge pressure (15 PSI), water flow rate (0.5 L/s), and pump head (1.38 mH₂O). These optimizations reduced system inefficiencies, such as backflow and turbulence, and enhanced the kit’s ability to replicate real-world operating conditions. The improved training kit provides students with a reliable tool for practical learning, bridging theoretical concepts with real-world applications in fluid mechanics. This study underscores the importance of continual enhancement of laboratory teaching tools to support effective education and industrial relevance.